Impact of cognitive taxing task towards working memory of video gamers and non-gamers / Amielia Natasya Mohd Zaid ... [et al.]. - Mohd Zaid, Amielia Natasya; Mohd Pozi, Muhammad Ariff Munshir; Zainuddin, Muhammad Haiqal; Mohd Nizam, Muhammad Hariz; Zani, Muhammad Isamuddin; Mazaulan, Mardiana; Mohamed, Muhamad Noor (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study examines the effects of cognitive taxing tasks on working memory among gamers and non-gamers. By investigating performance disparities between these groups, the research highlights the potential cognitive advantages linked to gaming by emphasizing working memory as a critical cognitive function, this study aims to uncover how gaming experience may shape resilience to mental fatigue induced by demanding tasks [1].